2006
DOI: 10.1142/s1464333206002372
|View full text |Cite
|
Sign up to set email alerts
|

What Is Wrong With Eia and Sea Anyway? A Sceptic's Perspective on Sustainability Assessment

Abstract: Environmental impact assessment (EIA) was initially introduced as an advocacy instrument for the biophysical environment in project decision-making. Strategic environmental assessment (SEA) evolved with a similar mission for strategic level proposals. However, recent trends towards more integration, particularly in the context of sustainability assessment (SA) mean that social and economic aspects are now frequently considered on a par with the environment in impact assessment processes. There are indications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 17 publications
0
26
0
11
Order By: Relevance
“…This kind of SEA focuses more on the policy planning process [19,21] and the integration process [23], and aims to make policy planning more strategic [24]. The main transformation compared with impact-oriented SEA is that the environmental effects should be part of the policy planning composition; furthermore, some studies have concluded social and economic issues are also considerations that should be covered [35,36]. This strategic feature leads to a more flexible and integrated SEA process, and attempts to achieve environmental goals and strategies by various strategic methods.…”
Section: Strategic-oriented Seamentioning
confidence: 99%
See 2 more Smart Citations
“…This kind of SEA focuses more on the policy planning process [19,21] and the integration process [23], and aims to make policy planning more strategic [24]. The main transformation compared with impact-oriented SEA is that the environmental effects should be part of the policy planning composition; furthermore, some studies have concluded social and economic issues are also considerations that should be covered [35,36]. This strategic feature leads to a more flexible and integrated SEA process, and attempts to achieve environmental goals and strategies by various strategic methods.…”
Section: Strategic-oriented Seamentioning
confidence: 99%
“…The former is the common understanding of sustainability [52], which considers the environmental, social, and economic aspects separately in the impact assessment process. However, some advocators reject any trade-off between natural resources and other socioeconomic objectives [26,53], and believe that sustainability should involve integrated and system-based thinking [35]. Gibson [36] also proposed the integrated principles of sustainability for sustainability assessment.…”
Section: Complexity In Environmental Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by several authors (Younge & Fowkes, 2003;Stringer et al, 2007;Richards et al, 2004), increase in public participation has been linked to public skepticism of the complex, uncertain and impactful nature of environmental decision-making. This spike in public participation is also attributed to a more evidence-based policy making to achieve an understanding of the process, and its implications emerged (Morrison-Saunders & Fischer, 2006), one of them is EIA (Bawole, 2013). Public participation in impact assessment primarily aims to understand community perceptions regarding the proposed activity and to resolve conflicts and reach consensus regarding that activity (Furia & Wallace-Jones, 2000).…”
Section: Public Participation In Environmental Managementmentioning
confidence: 99%
“…However, when integrating different aspects that may pull in different directions, experience has shown that caution is required in order for bio-physical aspects not being systematically traded off for e.g. economic related social or health issues (Morrison-Saunders and Fischer 2006).…”
Section: Editorialmentioning
confidence: 99%